Materials and processes for organic photovoltaic devices - Lento, Raffaella; Carbone, Vincenzo; Golemme, Attilio (My University, 2017)
Conversion of solar energy into electricity is a promising alternative to the use of conventional energy resources. In this context, organic solar cells (OSCs) can offer an interesting alternative to wafer-sized and inorganic thin films technology, due to the solution and low-temperature processability of organic semiconductors and to the possibility of using flexible substrates. All these features contribute to decrease the costs of production of solar devices, although their power conversion efficiency is still low. The studies in this thesis intend to investigate several effects on the efficiency of polymeric solar cells. In particular, I focused my attention on a well-studied bulk heterojunction (BHJ) constituted of regio-regular poly(3-hexylthiophene) - P3HT - as a donor and the fullerene soluble derivate [6,6]-Phenyl C61 butyric acid methyl ester - PC60BM - as an acceptor. In this way, the effect of materials, innovative processing and device architecture could be explored for this optimized reference system. The first part of this dissertation discusses the preparation and characterization of novel electropolymerized and photoconductive thin films of cyclo-metallated complexes, with the aim to employ an intrinsic photoconductor as an anode buffer layer (ABL) between the P3HT:PC60BM active layer and the ITO electrode. A photoconductive compound could represent an appealing alternative to conventional semiconductors due to the improving of its electrical conductivity upon light absorption, i.e. during the working condition of a solar cell, for enhancing charge transport to the electrodes. The studied complexes contain Pd(II) or Pt(II) as a metal center, 2-phenylpyridine as cyclo-metallated ligand and a triphenylamino-substituted (TPA) electropolymerizable Shiff base as an ancillary ligand. Optimization of the electro-deposition conditions (on ITO) and studies on dynamics, morphology, stability, photoconducting and hole transport properties on the obtained thin films were conducted. Results on their application as ABL are presented. The second part of this thesis explores the possibility of exciting plasmonic responses in a multilayer hyperbolic metamaterial (HMM) structure, consisting of alternating layers of BHJ and aluminum. Indeed, one approach for improving the power conversion efficiency in these BHJ solar cells is based on improving the light absorption of the device. Novel HMM plasmonic configurations offer the possibility of engineering the absorption band of the resulting structure to achieve the desired absorption performances over a broad wavelength range. A complete characterization of the optical properties of the engineered one-bilayer structure is given, together with the analysis of the J-V characteristics curves of the plasmonic solar devices studied. The beneficial contribution of plasmonic designed metal thin layers is evident even with a single BHJ/Al bilayer that shows enhanced conversion performances with respect to the control devices. Preliminary results based on experimental and simulated data on the two-bilayer system are presented. While working on the photovoltaic applications of HMMs, a series of experimental observations on silver-based HMM were performed, which offered the opportunity to investigate other several interesting phenomena. Ag-based HMMs have been constructed with both BHJ and TiO2 as the dielectric. In the first case, the excitation of the so-called Ferrell-Berreman modes were observed. These modes are characterized by a high absorption at a specific wavelength and could be used in solar cell technology for improving absorption and, thus, efficiency. In the latter case, a specifically conceived dielectric layer based on unsintered TiO2, poly(vinylpyrrolidone) and a dye, led to a thermally-tunable HMM, a highly relevant result for practical applications of HMMs.
Dottorato di Ricerca in Scienze e Tecnologie Fisiche, Chimiche e dei Materiali. Ciclo XXIX
Keywords: Solar cells; Organic electronics; Photovoltaic